Consensus statement on the management of invasive candidiasis in Indian scenario - Shastri, Prakash; Nangia, Vivek; Sathe, Prachee; Pande, Rajesh; Abraham, Abi; Hegde, Ashit; Ansari, Abdul Samad; Kapoor, Dharmesh; Mandal, Amit; Jain, Alok; Dinaker, M.; Mohanty, Deepali; et al. (International Journal of Research in Medical Sciences, 2019)
Invasive fungal infections in critically ill patients are associated with increased morbidity and mortality. Candida species are among the most common causes of nosocomial bloodstream infections and of invasive infections in intensive care units (ICUs). The high mortality mandates early identification of invasive candidiasis which is vital to initiate appropriate and timely treatment and improve outcomes. Delaying the initiation of treatment could result in an increase in mortality which can be avoided by usage of more rapid diagnostic techniques. There are multiple diagnostic tests including culture and non-culture tests like 1,3-β-D-glucan and newer techniques like MALDI-TOF which are available to diagnose candidemia but each with their drawbacks. Additionally, there are various guidelines like IDSA and ESCMID on treatment which aim to minimize death, late complications from deep-seated candidiasis and rise of drug- resistant Candida strains. Through this consensus statement prepared by a panel of experts, all of whom are senior intensivists, infectious disease specialists and microbiologists, we aim to address the major aspects of management of invasive candidiasis in the Indian population as per the authors opinions, backed by published evidence and supported by the latest clinical guidelines.